AN EMPIRICAL ANALYSIS OF THE EFFECT OF ECONOMIC DEGLOBALIZATION ON RENEWABLE ENERGY CONSUMPTION IN ICELAND - Anjani, Angelica Mutiara; Setyaningrum, Idfi; Susanto, Celine Margaretha; Kartikasari, Cynthia Yohanna (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
Recent global disruptions have sparked growing interest in the consequences of shifting trends from globalization toward economic deglobalization. This study examines the relationship between economic deglobalization, measured by the economic dimension of the KOF Globalization Index, and renewable energy consumption. Using Johansen cointegration and a Vector Error-Correction Model (VECM), Impulse-Response Function and variance-decomposition analyses on annual Iceland data (1990–2021), the findings show that economic deglobalization Granger-predicts renewable energy consumption and has a significant long-run influence, and the FEVD results show that its contribution to renewable energy variance gradually grows over time. This paper contributes to understanding the interaction between the changing global economic integration patterns and renewable energy consumption in one of the highly renewable-dependent European countries.